If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(36) = x + 9(21) Multiply 7 * 36 252 = x + 9(21) Multiply 9 * 21 252 = x + 189 Reorder the terms: 252 = 189 + x Solving 252 = 189 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 252 + -1x = 189 + x + -1x Combine like terms: x + -1x = 0 252 + -1x = 189 + 0 252 + -1x = 189 Add '-252' to each side of the equation. 252 + -252 + -1x = 189 + -252 Combine like terms: 252 + -252 = 0 0 + -1x = 189 + -252 -1x = 189 + -252 Combine like terms: 189 + -252 = -63 -1x = -63 Divide each side by '-1'. x = 63 Simplifying x = 63
| -x^2-10x-6forx=3 | | 28+15/3+2 | | (x-3)(X+8)(3X-5)=0 | | -3(2x+1)=-6x+3 | | 655554x=46684635394 | | 2x-3/3=3 | | 1/9(2m+16)=1/3(2m+4) | | 30x+870=12000 | | 9x(-4-3)= | | (3x-2y)(8x+3y)= | | 10m+6(2)=12 | | 16/48=x/-12 | | 4+2w-3w=12 | | n+5(n-3)=7 | | K=9/5(k-273.15)+32 | | 200=5(x+20) | | 1-3k=4k+8-9k | | 3.5x+0.5x=8+4.5x | | 8(m-2)=3(m+3) | | X-4(x+2)=6-2x | | .2(x+59)-6=.4(3x+20) | | 15-y=11 | | 3.5+0.5=8+4.5 | | 9x-7=37-4x | | -3(x+6)=-9 | | 7(4-t)=-89 | | x+5-4x=-13 | | 1+7x+6=6x+2 | | 8(2x-5)=-2(x+1)+16 | | x+10+2x+4= | | 1000=180+2.50x | | x^2-200x-284=0 |